Injection Safety and Practices Following Needle Stick Injuries: An Occupational Risk to Health Care Providers in Gujarat - Shah, Harsh D; Shah, Bonny H; Solanki, Hiren R; Agarwal, Vijay R; Parmar, Priyank A; Narkhede, Kiran M (National Journal of Community Medicine, 2015)
Background: An occupational exposure to blood can result from percutaneous (needle stick or other sharps injury) and mucocutaneous injury (splash of blood or other body fluids into the eyes, nose or mouth), or blood contact with non-intact skin. Beside transmission of infectious diseases, it indirectly affects health care delivery services especially in developing countries where demand is high in compare with manpower resources. Materials and method: The study was a cross sectional conducted among health care workers from a district of Gujarat. During the study, only one injection per health worker was taken into the consideration for better analysis. Results: Out of 251, 147 (58.56%) had needle stick injury in last one year and majority health workers were nursing staff. It was found that there was significant association who had NSIs previously before one year and injuries within last year and injuries occurred while giving the injections (48%). Only 32% of HCWs had done reporting about their NSIs to the concern authority and 20% followed the protocols of post exposure prophylaxis guidelines. Conclusion: Under reporting and lack of sensitivity on needles tick injuries had layered up during the study along with safe injection practices. Close monitoring on injection practices, surveillance on NSIs by quality assurance committee and structured communication plan should be in place to avoid health worker at risk and hazard of needle stick injuries.